Predicting the Digestibility of Nutrients and Energy Values of 4 Breadfruit Varieties Based on Chemical Analysis - Appiah, F.; Oduro, I.; Ellis, W.O. (Pakistan Journal of Nutrition, 2012)
Different breadfruit varieties were analyzed to determine their chemical composition using standard procedures. The results were used to establish prediction equations of DDM, DMI, NEL and RFV. No significant differences were found in the tannin contents which ranged between 3.44 mg/100 g to 4.30 mg/100 g. Lignin content was highest in A. camansi (12.1%) compared to the least (3.54%; T. africana). T. africana had the highest DDM (78.51%) whereas A. camansi had the least (70.21%). DMI was highest in A. altilis (2.65% per body weight) and lowest in T. africana (1.72%/kg body weight). T. africana having the highest NEL (88.00 Mca/lb) was similar to A. heterophyllus (86.77 Mcal/lb) but higher than A. camansi. A. altilis had higher RFV (156.48) compared to A. camansi (137.13), A. heterophyllus (126.18) and T. africana (104.88). The breadfruit varieties have good chemical composition and digestibility and therefore vindicate their use as food and feed. The predictors for DDM were ADL, lignin, hemicelluloses and NDF. DDI was dependent on carbohydrate, fat ADF, hemicelluloses and NDF contents. On the other hand NEL was predictable from ADL, lignin and hemicelluloses while RFV was dependent on the carbohydrate, fat and NDF content. Predictive equations derived in this study could be used in estimating nutrient digestibility and energy if relevant chemical composition is known without doing expensive feeding trials.